Gestational age and maternal weight effects on fetal cell‐free DNA in maternal plasma. (9th May 2013) - Wang, Eric; Batey, Annette; Struble, Craig; Musci, Thomas; Song, Ken; Oliphant, Arnold; Chitty, Lyn S.; Bianchi, Diana W.
ABSTRACT Objective To determine the effects of gestational age and maternal weight on percent fetal cell‐free DNA (cfDNA) in maternal plasma and the change in fetal cfDNA amounts within the same patient over time. Methods The cfDNA was extracted from maternal plasma from 22 384 singleton pregnancies of at least 10 weeks gestation undergoing the HarmonyTM Prenatal Test. The Harmony Prenatal Test determined fetal percentage via directed analysis of cfDNA. Results At 10 weeks 0 days to 10 weeks 6 days gestation, the median percent fetal cfDNA was 10.2%. Between 10 and 21 weeks gestation, percent fetal increased 0.1% per week (p < 0.0001), and 2% of pregnancies were below 4% fetal cfDNA. Beyond 21 weeks gestation, fetal cfDNA increased 1% per week (p < 0.0001). Fetal cfDNA percentage was proportional to gestational age and inversely proportional to maternal weight (p = 0.0016). Of 135 samples that were redrawn because of insufficient fetal cfDNA of the initial sample, 76 (56%) had greater than 4% fetal cfDNA in the sample from the second draw. Conclusion Fetal cfDNA increases with gestation, decreases with increasing maternal weight, and generally improves upon a blood redraw when the first attempt has insufficient fetal cfDNA. © 2013 John Wiley & Sons, Ltd.